The Strategy Of Developing Character Education With School-based Management in SDN 1 Batu Kumbung - Fatahul Uyun, Muhammad; Sudirman, Sudirman; Nisa, Khairun (Jurnal Ilmiah Pendidikan Indonesia, 2020)
This research aims to describe the strategy of character education development in school-based management at SDN 1 Batu Kumbung. The method used is descriptive qualitative research which is analyzed in its natural context. The strategy conducted by the principal of the school becomes the subject of the research. The data is obtained from interviews, observations, and documentations. Miles and Huberman’s analytical model which is consisted of data reductions. Data displays and conclusion drawing/verification has been used to evaluated the data. The character educations at the SDN 1 Batu Kumbung is fostered through planning, implementing and monitoring. The strategy of character education development in school-based management is practiced through teaching, role model, dicide proriority character, praxis proriority, instinctive act, school daily routine, reflections activity, daily activities at home and community, consistent habituation, and make a activities with unique name. nol dedoro activities is superior program. The school implements character education continuously by providing role model, teaching and reinforcement to the members of the school community (teacher, students, and staff)